Efecto de un programa académico de lectura para el enfoque intercultural en los estudiantes de quinto de secundaria de la I.E. Virgen de Loreto 2023 - Vizcarra Bazan, Marcelo Junior (2025)
The present research entitled “EFFECT OF AN ACADEMIC READING PROGRAM FOR THE INTERCULTURAL APPROACH IN STUDENTS OF 5TH OF SECONDARY SCHOOL IN THE I.E ‘VIRGEN DE LORETO’ 2023”, had as general objective to evaluate the effect of the academic reading program for the intercultural approach by means of different texts in the I.E before mentioned. The present research has a quantitative approach. The population comprised 164 secondary school students, from which a sample of 60 was selected. Direct observation was used as a technique, measured through a Likert scale questionnaire (entry and exit test), which allowed standardizing the actions observed in the students of this institution. When the program was applied to the 5th grade students of Secondary School “VIRGEN DE LORETO”, a conclusive effect was established and obtained by the mean of the entrance test (107) and exit test (133) in the experimental group, in which it was concluded that the intercultural approach did presented an effect in the 5th grade students of Secondary School “VIRGEN DE LORETO” developing identity, cognitive skills and fostering a pleasant environment for people with ethnic traits in the students participating in the educational program, managing to generate awareness of respect and equity that seeks to develop the intercultural approach.